Scientific Initiation as an instrument to promote the active learning of students in the classroom (Research, Society and Development, 2020)
Currently, in higher education, there is a constant search for teaching resources that are capable of promoting active learning. This article aims to analyze the use of scientific initiation as an instrument to promote active learning in the classroom. This qualitative study involves a teaching report based on teaching experience lived in 2018 in the subjects "Scientific Research Methodology" and "Information Systems", both offered in the Computer Science course at the Federal University of Pampa. In these subjects, among other activities, the teacher played the role of scientific initiation advisor, leading students to perform tasks such as: researching themes of the subject, identifying a research problem, conducting a bibliographic survey and preparing the scientific work for publication. The students were instructed to carry out the bibliographic survey in the annals of the International Teaching, Research and Extension Exhibition - SIEPE, as the proposed themes have been the themes of recurring publications in the referred event. It was suggested to students that, after the research was completed, it should be published in SIEPE. The students of the subject "Methodology of Scientific Research" produced seven papers, three of which were published in SIEPE. The students of the subject "Methodology of Scientific Research" produced seven papers, three of which were published in SIEPE. The “Information Systems” class, on the other hand, carried out eight works, four of which were published at that event. This article highlights that the strategy of relating themes of the programmatic content of the subject to research problems can promote the active learning of students in the classroom and instigate scientific initiation.